The Functions of Public Procurement – the Administrative Body as a „Smart Client” - Piotrowska, Aldona (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Administrative functions make up a particular type of system that fulfills a creative role with regard to social relations. The changing perspective on the functions of the state has meant that public procurement can perform a variety of functions. Analysis of legal standards, jurisprudence, and European Commission recommendations shows that the following public procurement functions are performed:– economic functions – orders are rational and public funds are used efficiently;– social functions – serve to realise social objectives, shape the social order and civicsociety;– eco-friendly functions – are used to achieve environmental goals;– innovation functions – serve pro-innovation objectives (especially pre-commercial procurement).The main goal of public procurement is to optimally use public funds. To make that happen, the administration should act as a „smart client” and use a variety of public procurement functions.